Operating Carbon-Neutral Tourism: Systematic Review & Bibliometric Analysis - J. P. R. C. Ranasinghe; R. A. D. D. N. Ranatunga; P. G. S. S. Pattiyagedara (Journal of Sustainable Tourism and Entrepreneurship, 2022)
Purpose: The primary goal is to identify the existing knowledge on carbon-neutral tourism gained from 2005 to 2023. Research Methodology: To accomplish the research purpose, a systematic literature review (SLR) approach and preferred reporting items for systematic reviews and Meta-analysis (PRISMA) guidelines were used to address the research objective. Through methodical literature research, bibliometric analysis, and the use of the VOS viewer software, all chosen papers were thoroughly reviewed, summarized, and synthesized. Results: Combining The Google Scholar, Emerald Insight, and Lens.ORG databases resulted in 43 articles. An increasing variety of tourism destinations are planning to become "carbon neutral" as pressure on the tourism industry to reduce greenhouse gas emissions grows. This is because tourism is now widely acknowledged as a significant contributor to global climate change due to the significant greenhouse gas emissions associated with air travel. Overlay visualization shows that there has been a high demand for carbon-neutral tourism since 2021. Contributions: They want to minimize their impact on global warming while simultaneously expanding their tourism industries by enhancing their reputation as green, environmentally conscious, and sustainable destinations.